Sarkosyl differentially solubilizes patient-derived alpha-synuclein fibril strains - Gram, Hjalte; Theologidis, Vasileios; Boesen, Thomas; Jensen, Poul Henning (Frontiers in Molecular Biosciences, 2023)
Insoluble α-synuclein (αSyn) filaments in brain tissue are a hallmark of Parkinson’s disease (PD) and Multiple system atrophy (MSA), and for structural studies, they have for decades been extracted using the detergent sarkosyl. We asked if PD and MSA patient-derived αSyn filament strains display different stability to sarkosyl extraction as this may confound our interpretation of the landscape of structural strains present in patients’ tissue. We compared the stability of cerebrospinal fluid-derived strains from four PD and four MSA patients using sedimentation and immunoassays and tested the seeding competence and strain-specific characteristics of the sarkosyl-soluble fractions using a seed amplification assay (SAA) and Thioflavin T (ThT) fluorescence. We demonstrate that filaments from PD are less resistant to sarkosyl than from MSA after they have been subjected to freezing and sonication. An enhanced release of monomers from PD filaments was the major difference between PD and MSA, but the sarkosyl-soluble fraction released from both PD and MSA filaments contained aggregates that displayed aggregate-specific epitopes and seeding activity with preserved disease-specific strain characteristics. Our results demonstrate that sarkosyl differentially destabilizes patient derived αSyn filament strains, which may compromise our ability to fully appreciate the landscape of αSyn filament currently being uncovered by high resolution cryoEM analyses. This should motivate an effort to develop more gentle extraction protocols.